Strategi pengembangan kawasan ekowisata dengan menggunakan model Community based ecotourism (CBE) di desa Kuala Terusan Kabupaten Pelalawan - Megawati Hari Dwi Jayanti; Sofyan Husein Siregar; Deni Efizon (Jurnal Zona, 2019)
Community-based ecotourism is one of the efforts in rural development to improve the local economy. The purpose of this study is to analyze the potential for community-based ecotourism development (CBE) in terms of ecological aspects (flora and fauna characteristics, Carrying capacity and waste management) and socio-economic aspects of culture and local community wisdom and formulate CBE development strategies. The study was conducted in April to July 2019 in the area of natural attractions in the village of Kuala Terusan Pelalawan Regency. The method in this study uses a survey method with a qualitative approach. The results of this study are that the flora found in Kuala Terusan is a type of peat forest and freshwater swamp forest so that there are no special flora that are characteristic of the Kuala Terusan Village area, fauna types in Kuala Terusan are reptile animals, mammals, birds and fish species that exist in the Kampar River. Based on the calculation of physical carrying capacity (Physical Carrying Capacity / PCC) PCC values obtained for swimming / snorkeling activities can accommodate 40 people / day. Activities carried out by Kuala Terusan tourist visitors are accompanied by beach tours and family picnics. The family picnic and beach tourism site has a utilization area of 3,000 m2. Carrying capacity that can accommodate tourists for beach tourism activities is 240 people / day. Facilities still need improvements such as in the processing of waste that has not been going well. CBE development strategies that can be carried out include planning CBE development programs, increasing stakeholder knowledge and awareness, formulating the concept of ecotourism with the government and involving community groups, developing food (local snacks typical of the Kuala Terusan region), improving the economy of local communities, utilizing the important issues of natural forest and the sustainability of nature, utilizing and enforcing existing regulations to support the community-based ecotourism development program at Kuala Terusan Village.